Monetary and Macroprudential Policy in an Estimated DSGE Model of the Euro Area - Quint, Dominic (IMF Working Papers; Working Paper ;, 2013)
In this paper, we study the optimal mix of monetary and macroprudential policies in an estimated two-country model of the euro area. The model includes real, nominal and financial frictions, and hence both monetary and macroprudential policy can play a role. We find that the introduction of a macroprudential rule would help in reducing macroeconomic volatility, improve welfare, and partially substitute for the lack of national monetary policies. Macroprudential policy would always increase the welfare of savers, but their effects on borrowers depend on the shock that hits the economy. In particular, macroprudential policy may entail welfare costs for borrowers under technology shocks, by increasing the countercyclical behavior of lending spreads.